1988
DOI: 10.1182/blood.v72.1.362.362
|View full text |Cite
|
Sign up to set email alerts
|

Platelet IgG, IgA, IgM, and albumin: correlation of platelet and plasma concentrations in normal subjects and in patients with ITP or dysproteinemia

Abstract: IgG, IgA, IgM, and albumin are primarily known as plasma proteins. Their presence in platelets is poorly understood. The total platelet content of IgG, IgA, and albumin, measured in solubilized platelets by an enzyme-linked immunosorbent-assay (ELISA) technique, was greater than 90% secreted after stimulation by thrombin, consistent with an alpha-granule location. The platelet concentrations of these proteins correlated with their plasma concentrations in normal subjects and over a wide range of abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…A positive correlation between serum and platelet values was found in ATP patients, suggesting non-specific absorbtion, but not in the three immune complex thrombocytopenic cohorts. The lack of a positive correlation between serum IgG and PAIgG in ATP patients was consistent with the observations of George & Saucerman (1988), who found no correlation between platelet surface IgG and serum IgG in ATP, dysproteinaemias and normal subjects studied, despite a correlation between their total platelet IgG and serum IgG. However, despite the correlation of serum and total platelet IgG there was no correlation between total platelet IgG and surface IgG.…”
Section: Discussionsupporting
confidence: 90%
“…A positive correlation between serum and platelet values was found in ATP patients, suggesting non-specific absorbtion, but not in the three immune complex thrombocytopenic cohorts. The lack of a positive correlation between serum IgG and PAIgG in ATP patients was consistent with the observations of George & Saucerman (1988), who found no correlation between platelet surface IgG and serum IgG in ATP, dysproteinaemias and normal subjects studied, despite a correlation between their total platelet IgG and serum IgG. However, despite the correlation of serum and total platelet IgG there was no correlation between total platelet IgG and surface IgG.…”
Section: Discussionsupporting
confidence: 90%
“…l i e immunoglobulins and albumin which are present in the a-granules in similar concentration as in plasma. Concerning fibrinogen, the concentration of which is 10 times higher in the a-granules than in the plasma (George & Saucerman, 1988), recent data have shown that its uptake is receptormediated and can be inhibited by antibody blocking of Gp IIb/IIIa (Harrison et al, 1992) and by barbourin, a desintegrin derived from venom viper which binds to platelet integrin an& (Handagama et al, 1993), showing that the primary receptor that mediates endocytosis for fibrinogen is cq&.…”
Section: Discussionmentioning
confidence: 99%
“…We also show, for the first time, that immunoglobulins may be present in human bone marrow MK. Because immunoglobulins enter MK through fluid‐phase endocytosis, the concentration of these molecules in MK is proportional to plasma levels ( George et al , 1990 ), whereas fibrinogen, which enters through receptor‐mediated endocytosis ( George et al , 1990 ; George & Saucerman, 1988; Handagama et al , 1993 ), is highly concentrated. It was therefore of interest to study MK from patients with increased levels of circulating immunoglobulins such as those with multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…This uptake is probably regulated by the integrin receptor α IIb ÎČ 3 ( Handagama et al , 1993 , 1995), the platelet receptor for fibrinogen. Other plasma proteins such as immunoglobulins and albumin can also enter MK α‐granules through fluid‐phase endocytosis ( George & Saucerman, 1988; George et al , 1985 ; Handagama et al , 1990 ).…”
mentioning
confidence: 99%